Truths and Lies in the Middle East Memoirs of a Veteran Journalist, 1952-2012. - Rouleau, Eric (The American University in Cairo Press, 2019)
Born in Cairo to an Egyptian Jewish family, Eric Rouleau was one of the most celebrated journalists of his generation, a status he owed to his extraordinary career, which began when the director of Le Monde charged him in the early 1960s with covering the Near and Middle East. Rouleau was a chief witness to the wars of 1967 and 1973 and was to meet all the major players, including Nasser, Levi Ashkol, Moshe Dayan, Golda Meir, Yasser Arafat, Ariel Sharon, and Anwar Sadat, painting striking portraits of each. More than a memoir, his book presents a history, lived from the inside, of the Israel-P.